Die zwei Gesichter einer Frau weil die Liebe ewig dauert ... - Delli Colli, Tonino 1923-2005; Zapponi, Bernardino 1927-2000; Schneider, Romy 1938-1982; Mastroianni, Marcello 1924-1996; Meineke, Eva Maria 1923-2018 (Kinowelt Home Entertainment, 2004)
Over two decades after their affair ended, a married man is haunted by the presence of his former lover.
Original: Italien, Deutschland, Frankreich, Monaco 1981
Bildformat: 1:1,85 (Letterbox)
Extras: Trailer, Starinfos
Keywords: Film; DVD-Video